2019
DOI: 10.4236/tel.2019.94058
|View full text |Cite
|
Sign up to set email alerts
|

Cointegration Analysis of Agricultural Growth and Financial Inclusion in Ghana

Abstract: Agriculture remains the foundation of economic growth for any economy irrespective of their level of development. Being aware of the imperative role of finance in the endogenous growth model, it is admitted that access and usage of finance is critical for the growth of the agriculture sector. Access to and usage of financial services would enable the incorporation of rural farmers into the financial system. In the light of this revelation, this paper examined Cointegration Analysis of Agricultural Growth and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
1
10
0
1
Order By: Relevance
“…By implication, an increase in access to financial services leads to a rise in farm productivity. As argued by Agbenyo et al (2019) access to financial services such as low lending interest rates would manipulate the cost of borrowing, savings, and purchasing of farm inputs for the expansion of agriculture production hence improving agriculture productivity. The paper also observed that gender had a significant effect on agricultural productivity as more males were believed to achieve higher productivity than their female counterparts.…”
Section: Conclusion and Policy Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…By implication, an increase in access to financial services leads to a rise in farm productivity. As argued by Agbenyo et al (2019) access to financial services such as low lending interest rates would manipulate the cost of borrowing, savings, and purchasing of farm inputs for the expansion of agriculture production hence improving agriculture productivity. The paper also observed that gender had a significant effect on agricultural productivity as more males were believed to achieve higher productivity than their female counterparts.…”
Section: Conclusion and Policy Recommendationsmentioning
confidence: 99%
“…In contrast, only 5.9% are holders of a bank account, as recorded by Findex data. Agbenyo et al (2019) argues that developing countries such as Ghana and other African countries are confronted with a series of obstacles such as low output, restricted access to finance, poor roads, high-cost labor, and the absence of adequate risk management techniques and facilities such as agricultural insurance. However, accentuate that agriculture relics as the bedrock of growth to any economy regardless of their level of development.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to KINGU (2019) and BOJNEC & KNIFIC (2021), increased revenue allows for investments in human capital and health, which boosts productivity and economic growth. AGBENYO et al, (2019), in their contribution to the access to finance debate, established that understanding finance's function in the endogenous growth theory portrays that the agriculture sector's growth is dependent on access to financing. Access to financial services is also an essential to rural development, according to ABRAHAM &FONTA (2018) andFERTŐ et al, (2021).…”
Section: Introductionmentioning
confidence: 99%
“…1 Trend Analysis of Agricultural Output from 2009 to 2015 in Ghana. Source: Budget statement, 2016 (Adopted from Kwarase 2017;Agbenyo et al 2019) the economic viability of farm operations; and enhance finally the quality life of farmers and society in general.…”
mentioning
confidence: 99%